Chitosan-based antimicrobial filter media for point-of-use water treatment: a proof-of-concept study - Liping Pang; Aden Sadler; Micki Bell; Sophie Harris; Erin McGill; Richard Sutton; Glenn Rowland; Mark P. Staiger (Environmental Science and Pollution Research, 2026)

Granule size-dependent biotransformation of organic micropollutants in aerobic granular sludge under different bioconversion conditions - Zhaolu Feng; Silvana Quiton Tapia; Froukje van Hees; Heike Schmitt; Mark C.M. van Loosdrecht; Nora B. Sutton (Journal of Hazardous Materials, 2026)

Natural capital enhances farm production, profitability and financial resilience: findings from a study on 230,000 ha of farmland in Australia - Elizabeth Heagney; Daniel Gregg; Dan Hill; James Radford; Grace Sutton; Fred Rainsford; Daniel O'Brien; Angela Hawdon; Imogen Semmler; Mark Gardner; Milly Taylor; Sue Ogilvy (Agricultural Systems, 2026)

Review of Nano-clay Polymer Composites for Controlled Nitrogen Release: Prospects and Limitations - Bitish Kumar Nayak; Dibyendu Chatterjee; Ranjan Paul; Saikat Ranjan Das; Totan Adak; Nintu Mandal; Julia Drewer; Abhijit Pradhan; Manik Chandra Kundu; Asit Kumar Pal; Gour Hari Santra; Suryakanta Sahoo; et al. (Agricultural Research, 2025)
This review paper discusses the potential and limitations of polymer composites for smart nitrogen (N) supply to meet the needs of agricultural crops. Unlike most conventional fertilizers, nano-clay polymer composites (NCPCs) offer a slow-release mechanism that enhances nitrogen use efficiency and reduces its loss to the environment. NCPCs are normally synthesized using solution blending, melt blending and in situ polymerization. Solution blending offers a better clay dispersion in the polymer matrix than melt blending owing to its low viscosity and strong stirring force. NCPCs have been characterized by several techniques, including equilibrium water absorbency, Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction and nutrient release kinetics. The potential benefits of using these composites are highlighted, including improved nitrogen use efficiency and reduced environmental impacts, as are their prospects for widespread use in agriculture and mitigation of the adverse environmental effects from conventional fertilizers. In addition, the limitations of NCPC technology, such as cost, scalability and potential negative environmental effects, are also investigated. The paper provides a wide perspective on the NCPC technology, including the regulatory environment and policy, industry trends and commercialization potential. NCPCs offer many benefits to increase nitrogen use efficiency and reduce pollution affecting water quality, air quality and climate. The main current barrier to overcome is to reduce production costs, so that farmers may also benefit financially from the higher nitrogen use efficiency and associated reduced amounts of nitrogen wasted to the environment.

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Removal of organic micropollutants under dry and wet weather conditions in a full-scale aerobic granular sludge plant - Zhaolu Feng; Heike Schmitt; Mark C M van Loosdrecht; Nora B Sutton (Water Research, 2025)

Modelling pollutants transport scenarios based on the X-Press Pearl disaster - Julia Rulent; Molly K. James; Ponnambalam Rameshwaran; Jennifer E. Jardine; Anna Katavouta; Sarah Wakelin; Ruchira Jayathilaka; Kanapathipillai Arulananthan; Jason Holt; Mark A. Sutton; Yuri Artioli (Marine Pollution Bulletin, 2024)

Sludge size affects sorption of organic micropollutants in full-scale aerobic granular sludge systems - Zhaolu Feng; Heike Schmitt; Mark C M van Loosdrecht; Nora B Sutton (Water Research, 2024)

Leaching and volatilization of nitrogen in paddy rice under different nitrogen management - Majharul Islam; Md. Mizanur Rahman; Mohammad Saiful Alam; Robert Martin Rees; G. K. M. Mustafizur Rahman; Md. Giashuddin Miah; Julia Drewer; Arti Bhatia; Mark A. Sutton (Nutrient Cycling in Agroecosystems, 2024)

Trends and geographic variation in adverse impacts of nitrogen use in Europe on human health, climate, and ecosystems: A review - Wim de Vries; Maximillian Posch; Dave Simpson; Frank A.A.M. de Leeuw; Hans J.M. van Grinsven; Lena F. Schulte-Uebbing; Mark A. Sutton; Gerard H. Ros (Earth-Science Reviews, 2024)

The biological cropping hypothesis over evolutionary time: an experimental test - Euan N. Furness; Mark D. Sutton (Theoretical Ecology, 2024)
Ecological disturbance has been proposed to have a variety of effects on biodiversity. These mechanisms are well studied over shorter timescales through experimental manipulation of ecosystems, but the effect of disturbance on longer timescales, where evolutionary processes operate, is less well understood. This is at least in part because evolutionary processes are too slow to observe in experimental manipulations of ecosystems. Here, we use the Rapid Evolutionary Simulator system (REvoSim) to solve this problem. REvoSim is a spatially explicit, agent-based simulation tool that models both ecological and evolutionary processes and is capable of simulating many thousands of generations of evolution per hour in a population of up to 1 million organisms. We use REvoSim to evaluate the biological cropping hypothesis, which predicts that the non-selective culling of organisms from populations (“cropping”) can enhance diversity in those populations over long timescales by reducing the homogenising effects of competitive exclusion. Our experiments demonstrate that cropping alone can increase diversity within populations under certain circumstances: those where it has the net effect of reducing the selection pressure acting on those populations. However, intense cropping pressure may increase the selection pressure on organisms to reproduce rapidly, potentially offsetting the effects of reduced competitive exclusion on diversity. We also show that cropping alone is not sufficient to result in reproductive isolation within populations. This implies that, while cropping can maintain a high species diversity within an ecosystem, additional mechanisms must be invoked to generate that high diversity in the first instance.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Reducing the environmental impact of rice production in subtropical India by minimising reactive nitrogen loss - Dibyendu Chatterjee; Saikat Ranjan Das; Sangita Mohanty; Baishnab Charan Muduli; Arti Bhatia; Bitish Kumar Nayak; Robert M. Rees; Julia Drewer; Amaresh Kumar Nayak; Tapan Kumar Adhya; Chidambaranathan Parameswaran; Jitendriya Meher; et al. (Journal of Environmental Management, 2024)

Estimation of ammonia deposition to forest ecosystems in Scotland and Sri Lanka using wind-controlled NH3 enhancement experiments - Ajinkya G. Deshpande; Matthew R. Jones; Netty van Dijk; Neil J. Mullinger; Duncan Harvey; Robert Nicoll; Galina Toteva; Gothamie Weerakoon; Sarath Nissanka; Buddhika Weerakoon; Maude Grenier; Agata Iwanicka; et al. (Atmospheric Environment, 2024)

Co-applied Nitrogen and Auxin via Nano-clay-Polymer Composites Enhances Yield and Nitrogen Use Efficiency - Dibyendu Chatterjee; Totan Adak; Bitish Kumar Nayak; Ranjan Paul; Abhijit Pradhan; Mark A. Sutton; Julia Drewer; Saikat Ranjan Das; Amaresh Kumar Nayak; Himanshu Pathak (Journal of Soil Science and Plant Nutrition, 2023)

The impact of different fertiliser management options and cultivars on nitrogen use efficiency and yield for rice cropping in the Indo-Gangetic Plain: Two seasons of methane, nitrous oxide and ammonia emissions - Arti Bhatia; Nicholas J. Cowan; Julia Drewer; Ritu Tomer; Vinod Kumar; Shikha Sharma; Ankita Paul; Niveta Jain; Sandeep Kumar; Girish Jha; Renu Singh; Radha Prasanna; et al. (Agriculture, Ecosystems & Environment, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Lichens as spatially transferable bioindicators for monitoring nitrogen pollution - Jay Delves; Jason E.J. Lewis; Niaz Ali; Saeed A. Asad; Sudipto Chatterjee; Peter D. Crittenden; Matthew Jones; Aysha Kiran; Bishnu Prasad Pandey; David Reay; Subodh Sharma; Dendup Tshering; et al. (Environmental Pollution, 2023)

Population estimates of photo-identified individuals using a modified POPAN model reveal that Raja Ampat’s reef manta rays are thriving - Edy Setyawan; Ben C. Stevenson; Mark V. Erdmann; Abdi W. Hasan; Abraham B. Sianipar; Imanuel Mofu; Mochamad I. H. Putra; Muhamad Izuan; Orgenes Ambafen; Rachel M. Fewster; Robin Aldridge-Sutton; Ronald Mambrasar; et al. (Frontiers in Marine Science, 2022)
The 6.7-million-hectare Raja Ampat archipelago is home to Indonesia’s largest reef manta ray ( Mobula alfredi ) population and a representative network of nine marine protected areas (MPAs). However, the population dynamics of M. alfredi in the region are still largely unknown. Using our photo-identification database, we fitted modified POPAN mark-recapture models with transience and per capita recruitment parameters to estimate key demographic characteristics of M. alfredi from two of Raja Ampat’s largest MPAs: Dampier Strait and South East (SE) Misool. A total of 1,041 unique individuals were photo-identified over an 11-year period (2009–2019) from Dampier Strait (n = 515) and SE Misool (n = 536). In our models, apparent survival probabilities and per capita recruitment rates were strongly linked with El Niño–Southern Oscillation (ENSO) events. Our models also estimated high apparent survival probabilities and significant increases in (sub)population sizes in both MPAs over a decade. In Dampier Strait, the estimated population size increased significantly (p = 0.018) from 226 (95% CI: 161, 283) to 317 (280, 355) individuals. Likewise, the estimated population size in SE Misool increased significantly (p = 0.008) from 210 (137, 308) to 511 (393, 618) individuals. Regardless of variation in the percentage change in population size between years throughout the study, the estimated overall population change shows a compound growth of 3.9% (0.7, 8.6) per annum in Dampier Strait and 10.7% (4.3, 16.1) per annum in SE Misool. Despite the global decline in oceanic sharks and rays due to fishing pressure in the last five decades, our study demonstrates the positive impact of a suite of long-term conservation efforts, coupled with the influence of ENSO events, on increasing M. alfredi abundance in Raja Ampat MPAs. Our study also underscores the importance of long-term monitoring to evaluate the effectiveness of conservation management measures on manta ray populations. Our modification of the standard POPAN model by incorporating per capita recruitment and transience parameters represents an important advance in mark-recapture modelling that should prove useful when examining other manta ray populations and other highly migratory species that are likely to have a substantial percentage of transient individuals.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

What the pluck? The theft of mammal hair by birds is an overlooked but common behavior with fitness implications - Henry S. Pollock; Sean E. MacDonald; Jeferson Vizentin‐Bugoni; Jeffrey D. Brawn; Zachary S. Sutton; Mark E. Hauber (Ecology, 2021)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Reproductive Ecology of Dragonfishes (Stomiiformes: Stomiidae) in the Gulf of Mexico - Alex D. Marks; David W. Kerstetter; David M. Wyanski; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Covariations between plant functional traits emerge from constraining parameterization of a terrestrial biosphere model - Marc Peaucelle; Cédric Bacour; Philippe Ciais; Nicolas Vuichard; Sylvain Kuppel; Josep Peñuelas; Luca Belelli Marchesini; Peter D. Blanken; Nina Buchmann; Jiquan Chen; Nicolas Delpierre; Ankur R. Desai; et al. (Global Ecology and Biogeography, 2019)
Aim The mechanisms of plant trait adaptation and acclimation are still poorly understood and, consequently, lack a consistent representation in terrestrial biosphere models (TBMs). Despite the increasing availability of geo‐referenced trait observations, current databases are still insufficient to cover all vegetation types and environmental conditions. In parallel, the growing number of continuous eddy‐covariance observations of energy and CO 2 fluxes has enabled modellers to optimize TBMs with these data. Past attempts to optimize TBM parameters mostly focused on model performance, overlooking the ecological properties of ecosystems. The aim of this study was to assess the ecological consistency of optimized trait‐related parameters while improving the model performances for gross primary productivity (GPP) at sites. Location Worldwide. Time period 1992–2012. Major taxa studied Trees and C 3 grasses. Methods We optimized parameters of the ORCHIDEE model against 371 site‐years of GPP estimates from the FLUXNET network, and we looked at global covariation among parameters and with climate. Results The optimized parameter values were shown to be consistent with leaf‐scale traits, in particular, with well‐known trade‐offs observed at the leaf level, echoing the leaf economic spectrum theory. Results showed a marked sensitivity of trait‐related parameters to local bioclimatic variables and reproduced the observed relationships between traits and climate. Main conclusions Our approach validates some biological processes implemented in the model and enables us to study ecological properties of vegetation at the canopy level, in addition to some traits that are difficult to observe experimentally. This study stresses the need for: (a) implementing explicit trade‐offs and acclimation processes in TBMs; (b) improving the representation of processes to avoid model‐specific parameterization; and (c) performing systematic measurements of traits at FLUXNET sites in order to gather information on plant ecophysiology and plant diversity, together with micro‐meteorological conditions.

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Potential Applicability of Persuasive Communication to Light-Glow Reduction Efforts: A Case Study of Marine Turtle Conservation - Ruth L. Kamrowski; Stephen G. Sutton; Renae C. Tobin; Mark Hamann (Environmental Management, 2014)

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Estimating environmentally relevant fixed nitrogen demand in the 21st century - Wilfried Winiwarter; Jan Willem Erisman; James N. Galloway; Zbigniew Klimont; Mark A. Sutton (Climatic Change, 2013)

Dry deposition of ammonia gas drives species change faster than wet deposition of ammonium ions: evidence from a long‐term field manipulation - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; John Neil Cape; Alan Crossley; Sarah Leeson; Mark A. Sutton; Netty van Dijk; David Fowler (Global Change Biology, 2011)
Although the effects of atmospheric nitrogen deposition on species composition are relatively well known, the roles of the different forms of nitrogen, in particular gaseous ammonia ( NH 3 ), have not been tested in the field. Since 2002, we have manipulated the form of N deposition to an ombrotrophic bog, W him, on deep peat in southern S cotland, with low ambient N (wet + dry = 8 kg N ha −1 yr −1 ) and S (4 kg S ha −1 yr −1 ) deposition. A gradient of ammonia ( NH 3 , dry N ), from 70 kg N ha −1 yr −1 down to background, 3–4 kg N ha −1 yr −1 was generated by free air release. Wet ammonium ( NH 4 + , wet N) was provided to replicate plots in a fine rainwater spray ( NH 4 Cl at +8, +24, +56 kg N ha −1 yr −1 ). Automated treatments are coupled to meteorological conditions, in a globally unique, field experiment. Ammonia concentrations were converted to NH 3 ‐ N deposition (kg N ha −1 ) using a site/vegetation specific parameterization. Within 3 years, exposure to relatively modest deposition of NH 3 , 20–56 kg NH 3 ‐N ha −1 yr −1 led to dramatic reductions in species cover, with almost total loss of C alluna vulgaris , S phagnum capillifolium and C ladonia portentosa . These effects appear to result from direct foliar uptake and interaction with abiotic and biotic stresses, rather than via effects on the soil. Additional wet N by contrast, significantly increased C alluna cover after 5 years at the 56 kg N dose, but reduced cover of S phagnum and C ladonia . Cover reductions caused by wet N were significantly different from and much smaller than those caused by equivalent dry N doses. The effects of gaseous NH 3 described here, highlight the potential for ammonia to destroy acid heathland and peat bog ecosystems. Separating the effects of gaseous ammonia and wet ammonium deposition, for a peat bog, has significant implications for regulatory bodies and conservation agencies.

Reactive nitrogen and greenhouse gas flux interactions in terrestrial ecosystems - Per Ambus; Ute Skiba; Klaus Butterbach-Bahl; Mark A. Sutton (Plant and Soil, 2011)

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Abundance and movement patterns of age-0 juvenile lake sturgeon in the Peshtigo River, Wisconsin - David C. Caroffino; Trent M. Sutton; Mark S. Lindberg (Environmental Biology of Fishes, 2009)

Argo: The Challenge of Continuing 10 Years of Progress - Dean Roemmich; Mathieu Belbéoch; Howard Freeland; Sylvia Garzoli; W. John Gould; Fiona Grant; Mark Ignaszewski; Brian King; Birgit Klein; Pierre-Yves Le Traon; Kjelle Mork; W. Brechner Owens; et al. (Oceanography, 2009)

The N-glycolyl form of mouse sialyl Lewis X is recognized by selectins but not by HECA-452 and FH6 antibodies that were raised against human cells - Junya Mitoma; Tatsuo Miyazaki; Mark Sutton-Smith; Misa Suzuki; Hideo Saito; Jiunn-Chern Yeh; Takehiro Kawano; Ole Hindsgaul; Peter H. Seeberger; Maria Panico; Stuart M. Haslam; Howard R. Morris; et al. (Glycoconjugate Journal, 2009)

Biotic, Abiotic, and Management Controls on the Net Ecosystem CO2 Exchange of European Mountain Grassland Ecosystems - Georg Wohlfahrt; Margaret Anderson-Dunn; Michael Bahn; Manuela Balzarolo; Frank Berninger; Claire Campbell; Arnaud Carrara; Alessandro Cescatti; Torben Christensen; Sabina Dore; Werner Eugster; Thomas Friborg; et al. (Ecosystems, 2008)

Uncertainties in the relationship between atmospheric nitrogen deposition and forest carbon sequestration - MARK A. SUTTON; DAVID SIMPSON; PETER E. LEVY; ROGNVALD I. SMITH; STEFAN REIS; MARCEL Van OIJEN; WIM De VRIES (Global Change Biology, 2008)
In a recent study, Magnani et al. report how atmospheric nitrogen deposition drives stand‐lifetime net ecosystem productivity (NEP av ) for midlatitude forests, with an extremely high C to N response (725 kg C kg −1 wet‐deposited N for their European sites). We present here a re‐analysis of these data, which suggests a much smaller C : N response for total N inputs. Accounting for dry, as well as wet N deposition reduces the C : N response to 177 : 1. However, if covariance with intersite climatological differences is accounted for, the actual C : N response in this dataset may be et al. Multisite regression of simulated NEP av vs. total N deposition reproduces a high C : N response (149 : 1). However, once the effects of intersite climatological differences are accounted for, the value is again found to be much smaller, pointing to a real C : N response of about 50–75 : 1.

Links between climate and recruitment of New Zealand hoki (Macruronus novaezelandiae) now unclear - R.I.C. Chris Francis; Mark G. Hadfield; Janet M. Bradford‐Grieve; James A. Renwick; Philip J. H. Sutton (New Zealand Journal of Marine and Freshwater Research, 2006)
We investigated the relationship between climate variation and year‐class strengths for hoki ( Macruronus novaezelandiae ) in New Zealand waters. Our analyses extended those of a previous study, by using an additional 6 years’ data and considering some additional predictands (total year‐class strength and proportion migrating) relating to an alternative stock‐structure hypothesis, and also updated them, by using revised versions of some predictors and year‐class strengths. Predictors considered were based on the Southern Oscillation Index, weather patterns, sea‐surface temperatures, wind speeds, and modelled mixed‐layer depths and nutrient concentrations. In contrast to the earlier analyses we found little or no predictive power for either year‐class strength or proportion migrating. The substantial correlations found in the earlier study were greatly reduced. Such reversals are not uncommon in the climate‐recruitment literature.

Re-engineering the target specificity of clostridial neurotoxins - a route to novel therapeutics - Keith A. Foster; Emily J. Adams; Lyndsey Durose; Caroline J. Cruttwell; Elizabeth Marks; Clifford C. Shone; John A. Chaddock; Clare L. Cox; Charlotte Heaton; J. Mark Sutton; Jonathan Wayne; Frances C. G. Alexander; et al. (Neurotoxicity Research, 2006)

Accurately measuring volcanic plume velocity with multiple UV spectrometers - Glyn Williams-Jones; Keith A. Horton; Tamar Elias; Harold Garbeil; Peter J. Mouginis-Mark; A. Jeff Sutton; Andrew J. L. Harris (Bulletin of Volcanology, 2006)

Real-time measurement of volcanic SO2 emissions: validation of a new UV correlation spectrometer (FLYSPEC) - Keith A. Horton; Glyn Williams-Jones; Harold Garbeil; Tamar Elias; A. Jeff Sutton; Peter Mouginis-Mark; John N. Porter; Steven Clegg (Bulletin of Volcanology, 2006)

Y Chromosome and Other Heterochromatic Sequences of the Drosophila Melanogaster Genome: How Far can we go? - A. Bernardo Carvalho; Maria D. Vibranovski; Joseph W. Carlson; Susan E. Celniker; Roger A. Hoskins; Gerald M. Rubin; Granger G. Sutton; Mark D. Adams; Eugene W. Myers; Andrew G. Clark (Genetica, 2003)

Establishing the Link between Ammonia Emission Control and Measurements of Reduced Nitrogen Concentrations and Deposition - Mark A. Sutton; Willem A. H. Asman; Thomas Ellermann; J. A. Van Jaarsveld; Karin Acker; Viney Aneja; Jan Duyzer; Laszlo Horvath; Sergey Paramonov; Marta Mitosinkova; Y. Sim Tang; Beat Achermann; et al. (Environmental Monitoring and Assessment, 2003)

In vivo glycosylation of MUC1 in airway epithelial cells - Howard S. Silverman; Mark Sutton-Smith; Paul Heal; Simon Parry; Timea Palmai-Pallag; Shih-Hsing Leir; Howard R. Morris; Anne Dell; Ann Harris (Glycoconjugate Journal, 2002)

Sustainable Management of Landfill Leachate by Irrigation - Mark S. Bowman; Timothy S. Clune; Bruce G. Sutton (Water, Air, & Soil Pollution, 2002)

Seasonal variability of apoplastic NH4 + and pH in an intensively managed grassland - Benjamin Loubet; Celia Milford; Paul W. Hill; Y. Sim Tang; Pierre Cellier; Mark A. Sutton (Plant and Soil, 2002)

FAB-MS characterization of sialyl Lewisx determinants on polylactosamine chains of human airway mucins secreted by patients suffering from cystic fibrosis or chronic bronchitis - Willy Morelle; Mark Sutton-Smith; Howard R. Morris; Monique Davril; Philippe Roussel; Anne Dell (Glycoconjugate Journal, 2001)

Advances in micrometeorological methods for the measurement and interpretation of gas and particle nitrogen fluxes - David Fowler; Mhairi Coyle; Chris Flechard; Ken Hargreaves; Eiko Nemitz; Robert Storeton-West; Mark Sutton; Jan-Willem Erisman (Plant and Soil, 2001)